2022
DOI: 10.1021/acs.energyfuels.2c00053
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Phosphorus in Ash during Cocombustion of Sewage Sludge and Coals: Influence of Coal and Steam

Abstract: Sewage sludge (SS) incineration technology has become a primary method to recover and reuse SS, and the cocombustion with coal is a more feasible process due to the limited heating value of wet SS and the difficulty of drying SS. Being that phosphorus is a major element in SS, its migration during cocombustion with coal was unclear but vital. Phosphorus migration during the cocombustion of wet SS and various coals was investigated by drop tube furnace in this study. More phosphorus was fixed as apatite in ash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Humans lack the ability to digest phytic acid, and a smaller fraction of the phosphorus content is therefore present in this form . However, most of the phosphorus is present as inorganic phosphorus, often aluminum- and/or iron-phosphates because iron- and aluminum-based additives are used as coagulation or precipitation agents in wastewater treatment processes. , Using chemical fractionation methods (the SMT protocol), it was shown that sewage sludge normally contain more than 70% inorganic phosphorus, out of which 60–95% was reported to be present as nonapatite phosphorus. , This includes, for example, Al- and Fe-phosphates. Solution state 31 P NMR analysis has shown similar results, and the phosphorus extracted for analysis was confirmed to be mainly orthophosphate. ,, However, some chemical fractionation studies (using the Hedley protocol) showed that more than 50% of the phosphorus is found in the acid-leachable (HCl) fraction, indicating phosphorus is associated as apatite in these sewage sludge samples. …”
Section: Phosphorus In Biomassmentioning
confidence: 99%
See 3 more Smart Citations
“…Humans lack the ability to digest phytic acid, and a smaller fraction of the phosphorus content is therefore present in this form . However, most of the phosphorus is present as inorganic phosphorus, often aluminum- and/or iron-phosphates because iron- and aluminum-based additives are used as coagulation or precipitation agents in wastewater treatment processes. , Using chemical fractionation methods (the SMT protocol), it was shown that sewage sludge normally contain more than 70% inorganic phosphorus, out of which 60–95% was reported to be present as nonapatite phosphorus. , This includes, for example, Al- and Fe-phosphates. Solution state 31 P NMR analysis has shown similar results, and the phosphorus extracted for analysis was confirmed to be mainly orthophosphate. ,, However, some chemical fractionation studies (using the Hedley protocol) showed that more than 50% of the phosphorus is found in the acid-leachable (HCl) fraction, indicating phosphorus is associated as apatite in these sewage sludge samples. …”
Section: Phosphorus In Biomassmentioning
confidence: 99%
“…The decomposition of organic phosphorus species in biomass has been studied primarily using solution state 31 P NMR ,,,,,, and chemical fractionation following the SMT protocol. , , …”
Section: Transformation Of Phosphorus In Biomass Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sewage sludge is a byproduct generated in the process of sewage treatment, which contains many organic pollutants, heavy metals, parasites, pathogens, and other substances harmful to the environment and human health. Due to rapid economic and social developments globally, the quantity of sludge produced has dramatically increased. Many countries have developed relevant policies regarding sludge treatment and disposal to encourage a reduction in its yield in a controllable way and render it harmless, with an eye toward transformation to useful products.…”
Section: Introductionmentioning
confidence: 99%